Switching to a Second TNF-α Inhibitor in a Patient with Severe Juvenile Polyarthritis: A Clinical Case - Ekaterina V. Denisova; Ekaterina I. Alexeeva; Tatyana M. Dvoryakovskaya; Margarita A. Soloshenko; Anna V. Mamutova; Kseniya B. Isayeva; Anna N. Fetisova ("Paediatrician" Publishers LLC, 2018)
Background. Insufficient efficacy or intolerance of the first TNF-α inhibitor in patients with juvenile idiopathic arthritis (JIA) is an indication for the appointment of a second inhibitor. Golimumab is a new TNF-α inhibitor registered for treating JIA under pediatric indications. Clinical Case Description. At an early age, the patient had an onset of polyarticular JIA. Due to the aggressive and rapidly progressive course, failure of therapy with nonsteroidal anti-inflammatory drugs, methotrexate and glucocorticosteroids for intra-articular administration, infliximab was prescribed to the patient, with a positive effect. Subsequently, the patient developed a secondary resistance to infliximab, inflammatory changes in the joints relapsed; thus, a second TNF-α inhibitor (golimumab) was prescribed. In the course of therapy, pain and signs of arthritis in the patient were reversed, and the range of motion in the affected joints increased. After one year of therapy, JIA remission was ascertained. At the same time, the child was not administered oral glucocorticosteroids. The duration of remission of the joint syndrome was 5 years. Adverse events were not serious and did not constitute a basis for drug discontinuation. Conclusion. Switching to a second TNF-α inhibitor (golimumab) was effective in a patient with a secondary resistance to the first TNF-α inhibitor.